Cytotoxic Effect of the Her-2/Her-1 Inhibitor PKI-166 on Renal Cancer Cells Expressing the Connexin 32 Gene - Eriko Fujimoto; Tomohiro Yano; Hiromi Sato; Kiyokazu Hagiwara; Hiroshi Yamasaki; Sumiko Shirai; Keiko Fukumoto; Hiromi Hagiwara; Etsuko Negishi; Koichi Ueno (Elsevier, 2005)
We have reported that connexin (Cx) 32 acts as a tumor suppressor gene in renal cancer cells partly due to Her-2 inactivation. Here, we determined if a Her-2/Her-1 inhibitor (PKI-166) can enhance the tumor-suppressive effect of Cx32 in Caki-2 cells from human renal cell carcinoma. The expression of Cx32 in Caki-2 cells was required for PKI-166-induced cytotoxic effect at lower doses. The cyctotoxicity was dependent on the occurrence of apoptosis and partly mediated by Cx32-driven gap junction intercellular communications. These results suggest that PKI-166 further supports the tumor-suppressive effect of the Cx32 gene in renal cancer cells through the induction of apoptosis. Keywords:: connexin 32, PKI-166, renal cancer cell